Auxin-mediated seed germination and crosstalk with other phytohormones - Ament, Anita; Kuchařová, Anna; Vladejić, Jovanka; Bělíček, Jakub; Brunoni, Federica; Novák, Ondřej (Frontiers in Plant Science, 2026)
Seed germination is a critical and highly regulated process that transitions a dormant seed to an actively growing seedling. This process plays a vital physiological role in regulating seedling establishment, plant growth, and development, while ecologically it shapes species distribution patterns, drives plant population dynamics, and influences ecosystem productivity. Seed germination is tightly controlled by various environmental and intrinsic factors, with phytohormones acting as primary mediators. Auxins, mainly indole-3-acetic acid (IAA), are involved in many aspects of plant growth and development. Accumulating evidence suggests that IAA modulates the balance between dormancy and germination similarly to abscisic acid (ABA) and gibberellins (GAs). In this mini-review, we summarize our current knowledge on the molecular mechanisms underlying the modulatory roles of IAA during seed germination. We specifically examine the crosstalk between IAA and other key phytohormones (ABA and GAs) that shape germination outcomes. Clarifying these interactions will enhance our understanding of the dormancy-germination switch and may offer practical methods to control germination timing in agriculture.